2023
DOI: 10.1093/rb/rbad112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serum proteins on corrosion rates and product bioabsorbability of biodegradable metals

Hongjie Zhang,
Xin Li,
Zehua Qu
et al.

Abstract: Corrodible metals are the newest kind of biodegradable materials and raise a new problem of the corrosion products. However, the removal of the precipitated products has been unclear and even largely ignored in publications. Herein, we find that albumin, an abundant macromolecule in serum enhances the solubility of corrosion products of iron in blood mimetic Hank’s solution significantly. This is universal for other main biodegradable metals such as magnesium, zinc and polyester-coated iron. Albumin also influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…The importance of three-dimensional (3D) extracellular matrix for epithelial cells is recognized, where the combination of topography and chemical microenvironment promotes normal epithelial polarity and differentiation . The physical and chemical properties of material surfaces can regulate adhesion, migration, proliferation, and differentiation of cells. Micropillar arrays provide a quasi-3D interface for cell-material interactions and have been demonstrated to be an appropriate platform to induce cell nuclear deformation. …”
Section: Introductionmentioning
confidence: 99%
“…The importance of three-dimensional (3D) extracellular matrix for epithelial cells is recognized, where the combination of topography and chemical microenvironment promotes normal epithelial polarity and differentiation . The physical and chemical properties of material surfaces can regulate adhesion, migration, proliferation, and differentiation of cells. Micropillar arrays provide a quasi-3D interface for cell-material interactions and have been demonstrated to be an appropriate platform to induce cell nuclear deformation. …”
Section: Introductionmentioning
confidence: 99%
“…For example, in pharmaceutical research, it has been found that drugs with different chirality have different biological activities and toxic effects [ 20 ]; at the molecular level, the functions exercised by biomolecules are often related to their configurations [ 21 ]. The same phenomenon exists in nanomaterials, where nanomaterials synthesized from the same monomer can form different microconfigurations with different properties, and thus, be used in different fields [ 22–24 ]. There have been some studies on the differentiation or proliferation of cells on scaffolds with different morphological features [ 25 ].…”
Section: Introductionmentioning
confidence: 99%